Bemisia tabaci: the whitefly vector of cassava mosaic geminiviruses in Africa: an ecological perspective - Legg, James P. (1994)
The ecology of the Bemisia tabaci/cassava/African cassava mosaic virus (ACMV) pathosystem is reviewed briefly with special attention given to the parameters affecting the pattern of population development of B. tabaci. Significant gaps in our understanding of this system remain, particularly concerning the importance of interactions of B. tabaci with other arthropod pests of cassava and the influence of ecological factors such as soil nutrients indirectly through their effects upon cassava. An holistic ecological approach to future work on B. tabaci as vector of ACMV is proposed.